Analisa Kinerja Bendung Wae Leman Desa Wae Tina Kecamatan Wae Lata Kabupaten Buru - Laputty, Asriani; Nara, Obednego Dominggus; Titaley, Henriette Dorothy (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Investments that enhance a nation's infrastructure include water structures, such as the Wae Leman Dam in Indonesia. The Wae Leman Dam, serving an area of 2500 hectares, is situated on the Wae Leman River in Buru Regency, Maluku Province. This extensive region necessitates optimal circumstances for dam construction and the upkeep of irrigation systems in the Wae Leman irrigation basin, particularly for this dam project. The Wae Leman Dam has not undergone maintenance since its construction in 2015, with plans for maintenance scheduled in 2023. Consequently, it is essential to perform a performance analysis of the Wae Leman dam to assess its physical condition, efficacy, and functionality at present. This study employs references from the Regulation of the Minister of Public Works and Public Housing Number 12/PRT/M/2015 regarding Irrigation Exploitation and Maintenance, which has been adapted into the Irrigation System Performance Index (IKSI) method to facilitate the evaluation of the condition and functionality of dam structures. The dam performance index assessment yielded a weight of 11.36%, which corresponds to 87.3% of the maximum weight of 13% for the Wae Leman Dam performance evaluation. This number signifies that the performance of the primary building system (dam) is satisfactory; the recommendations for re-optimizing the dam's function include repairs, routine maintenance, and periodic maintenance activities.